(untitled) (GAIMS Journal of Medical Sciences, 2025)
This case report details a rare presentation of cervical Ewing’s sarcoma in a 4-year-old female, emphasizing its clinical presentation, diagnostic process, and treatment challenges. The patient initially presented with a rapidly growing neck mass and neurological symptoms; MRI confirmed a well-defined mass at the C5-C6 vertebral level, and histopathological examination verified the diagnosis of Ewing’s sarcoma. Treatment involved neoadjuvant chemotherapy, followed by surgical resection with clear margins, and the patient is currently being monitored for recurrence with a guarded prognosis. This case underscores the need for a multidisciplinary approach, early intervention, and thorough surgical planning in managing rare and aggressive tumors in complex anatomical locations, contributing valuable insights to the limited literature on this uncommon malignancy.